(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper focuses on the influence of advertising communications on effectiveness of online advertising, based on the interactivity between consumers and advertisers. This study also focuses on the recent trends in Advertising Communication. In all fields of communication, the Internet is the latest information technology with the reputation of urgency and rapidity, thereby bringing globalization. Communication through the internet is more precise, with its users having a successful interactive strategy. Online advertising has taken new forms in recent days, gaining more advantages over conventional media such as print, television and radio. Communication in advertising is becoming accurate, intimate, interesting, interactive as well as social. On numerous social networking sites such as Facebook, Twitter and YouTube, various communication techniques are pursued. The review of the study focuses on the essence of advertisement research. Along with the Advertising Communication Model, this paper also focuses on emerging developments in marketing communications. The recent growth in customer reaction to ads has served as an impetus to explore the psychological dimensions of advertising research, since the data collected during advertising research helps address the question of how advertising actually works.